How Convenience, Usefulness, and Security Drive User Interest in Applications - Restya, Galuh Putri; Deviastri, Lily (SAN Scientific, 2025)
This research aims to determine whether convenience, usefulness and security have an individual and simultaneous influence on interest in using the GoPay application in the district. Cengkareng, West Jakarta. The independent variables of this research include convenience, usefulness and safety, while the dependent variable is interest in use. This research was carried out using quantitative methods. This research uses multiple linear regression analysis as a data analysis method with a significant level of 5%. The results of the analysis in this research explain that convenience, benefits and security positively and significantly and simultaneously influence interest in using the GoPay application in the district area. Cengkareng, West Jakarta. Managerial implications suggest that to attract and retain users, companies must focus on enhancing user convenience through intuitive design and seamless navigation, ensuring that the application offers valuable and practical features that meet user needs, and providing robust security measures to protect user data and build trust. By aligning application development and marketing strategies with these key user priorities, businesses can significantly increase user engagement and satisfaction, ultimately driving higher adoption rates and customer loyalty.